(untitled) (Biocenosis, 2022)
Mario Boza forged a strong alliance with the United States Peace Corps and actively sought volunteers for assistance during the early days of the development of the national parks system. Mario recognized the value of Peace Corps volunteers (PCVs) as they were university educated, had good command of Spanish and were willing to engage in any task requested of them while not protesting about discomforts. Mario initially recruited PCVs in the 1970s to help develop the infrastructure of the nascent National Park Service as well as to conduct biological inventories and historical documentation of the proposed parks. In the 1980s, Mario reached out to the Peace Corps once again for assistance in a national environmental education campaign to increase awareness of the need to protect wildlands and Costa Rica’s biodiversity.